Controllable synthesis of isoreticular pillared-layer MOFs based on N-rich triangular prism building units: gas adsorption and luminescent properties. (20th November 2018) - Xie, Wei; Yao, Chan; Shao, Kui-Zhan; Xu, Yan-Hong; Su, Zhong-Min
Abstract : Isoreticular1–4 MOFs with rarelon topologies have been rationally synthesized based on novel trigonal-prism building units. Abstract : A series of isoreticular MOFs (1–4 ) with rarelon topologies have been rationally synthesized using the ligand benzotriazole-5-carboxylic acid and auxiliary aromatic dicarboxylic ligands based on novel double secondary building units (SBUs) and trigonal-prism building units. On the other hand, MOFs1–4 all adopt pillared-layer structures based on the same honeycomb layers, and then the neighboring layers are linked together through the ditopic carboxylate pillars. They all exhibit similar constructions but different pore characteristics (volumes and surfaces), owing to convertible ditopic ligands pillaring the same layers. Notably, they all possess a certain degree of air and water stability and CO2 uptake capacity. In addition, we researched the luminescence properties of MOFs1–4 . We found that MOF2 can be used as a fluorescent probe for exhibiting a clear fluorescent enhancement "turn on" response for H2 O and a fluorescence quenching "turn-off" response for nitrobenzene (NB).